Effect of Covid-19 Pandemic on Women Entrepreneurial Sustainability and Post-Pandemic Opportunities - Naeem, Sunbul (South Asian Review of Business and Administrative Studies (SABAS), 2020)
The women entrepreneurs are important pillars of any economy. Without the active participant of the women’ entrepreneurs we cannot be economically establish in the recent crisis of the COVID-19. The governments of the world can promote the valor of the entrepreneurship among the women by adopting following recommendation. First each government should reshuffle their policies and introduced these policies in which a gender equality programs will be promoted.Every government should take an initiative to conduct the training to the young women with providing a stipend to each participant during these trainings. While providing the training to these women these governments should establish the women incubation business centers in these centers they provide such kind of the skills to these women which not only promote their confidence level among these participants but also promote their inner ability of the creativeness. The government should launch such rehabilitation programs for those women entrepreneurs who’ business are badly affect during this crisis, to provide them another business opportunity to re-established their business from grass-root level. For those women wo are interested to starts a new venture also provide them logistic and financial support for them and also provide the unique business ideas to these interested females-entrepreneurs as well. To financing the new project, the government should provide these finances to these women without any complicated procedures. They should provide the required funding’s to these women at their home steps. For the training purpose to these women the government should take the help from different expertise and NGO’s.It is necessary for all of us that we should learn lesson from this crisis and it is also very necessary that we should take drastic steps to promote the innovative skills among the young entrepreneurs of our society.